The Urgency of Wage Regulation for Gig Economy Workers in Indonesia - Encik Lukmanul Hakim (Rechtenstudent, 2025)
The advancement of digital technology has driven the emergence of a new work model known as the gig economy, particularly in Indonesia, characterized by the increasing number of freelance workers based on digital platforms. Despite offering flexibility, gig workers face serious challenges related to legal protection and fulfillment of labor rights, such as the lack of recognition of formal employment status and uncertainty of wage guarantees. This study examines the legal protection for gig workers from the perspective of labor law in Indonesia, comparing national regulations and practices in countries such as the United Kingdom and the Netherlands. The findings show that Indonesian regulations are inadequate to ensure fair protection for gig workers, thus policies regulating employment status, minimum wages, and inclusive social security are needed. Proper enforcement of legal protection is expected to create a fair and sustainable work ecosystem in the digital economy era.